Psicología del espacio: desarrollo del determinismo fenomenológico (2023)
In search of recovering the importance regarding the relationship of architecture with man, it is proposed to affect one of the most relevant and changing elements within a society such as behavior, based on the concern for the change in the behavior of a person, 2 currents are linked, such as architecture and psychology, to find the path towards behavioral change through the tools that architecture provides focused on 2 themes, which are determinism and phenomenology, which are correlated after an exhaustive analysis of the Both negative and positive emotions and influences in the subconscious of a person seek to generate a lived environment that accommodates the search for conscious experiences in order to generate reflection culminating in a process of behavioral change.